Evaluating the development and well-being assessment (DAWBA) in pediatric anxiety and depression - Paia Amelio; Chase Antonacci; Parmis Khosravi; Simone Haller; Katharina Kircanski; Erin Berman; Lisa Cullins; Krystal Lewis; Mollie Davis; Chana Engel; Kenneth Towbin; Argyris Stringaris; et al. (BMC, 2024)
Abstract Enhancing screening practices and developing scalable diagnostic tools are imperative in response to the increasing prevalence of youth mental health challenges. Structured lay psychiatric interviews have emerged as one such promising tool. However, there remains limited research evaluating structured psychiatric interviews, specifically their characterization of internalizing disorders in treatment-seeking youth. This study evaluates the relationship between the Development and Well-Being Assessment (DAWBA), a structured psychiatric interview, and established measures of pediatric anxiety and depression, including the Screen for Child Anxiety Related Disorders (SCARED), the Pediatric Anxiety Rating Scale (PARS), and the Mood and Feelings Questionnaire (MFQ). The study comprised two independent clinical samples of treatment-seeking youth: sample one included 55 youth with anxiety and 29 healthy volunteers (HV), while sample two included 127 youth with Major Depressive Disorder and 73 HVs. We examined the association between the DAWBA band scores, indicating predicted risk for diagnosis, the SCARED and PARS (sample one), and the MFQ (sample two). An exploratory analysis was conducted in a subset of participants to test whether DAWBA band scores predicted the change in anxiety symptoms (SCARED, PARS) across a 12-week course of cognitive behavioral therapy. The results revealed that the DAWBA significantly predicted the SCARED, PARS and MFQ measures at baseline; however, it did not predict changes in anxiety symptoms across treatment. These findings suggest that the DAWBA may be a helpful screening tool for indexing anxiety and depression in treatment-seeking youth but is not especially predictive of longitudinal trajectories in symptomatology across psychotherapy.